What is community control of schools? : a citizen fact sheet
Adapted from Preston R. Wilcox readings for local use by the trainin g center, Community Aiction Pittsburgh, Inc. and concerned citizens.
AR/MISR/123/2
English
Shelf no. 1.
Keywords: Community and school